2013
DOI: 10.3348/kjr.2013.14.4.607
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT Findings of Bowel Transection in Blunt Abdominal Trauma

Abstract: ObjectiveThough a number of CT findings of bowel and mesenteric injuries in blunt abdominal trauma are described in literature, no studies on the specific CT signs of a transected bowel have been published. In the present study we describe the incidence and new CT signs of bowel transection in blunt abdominal trauma.Materials and MethodsWe investigated the incidence of bowel transection in 513 patients admitted for blunt abdominal trauma who underwent multidetector CT (MDCT). The MDCT findings of 8 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The Janus sign refers to adjacent enhancing and nonenhancing loops of bowel. The Janus sign has been described as specific for bowel injury (42) (Figs 4, 5). Focal mucosal hyperenhancement of the bowel can be seen in bowel ischemia, particularly after reperfusion from an arterial injury (43).…”
Section: Indirect Findings Of Blunt Bowel and Mesenteric Injurymentioning
confidence: 99%
“…The Janus sign refers to adjacent enhancing and nonenhancing loops of bowel. The Janus sign has been described as specific for bowel injury (42) (Figs 4, 5). Focal mucosal hyperenhancement of the bowel can be seen in bowel ischemia, particularly after reperfusion from an arterial injury (43).…”
Section: Indirect Findings Of Blunt Bowel and Mesenteric Injurymentioning
confidence: 99%
“…The rate of surgical intervention would be raised 6-and 3-fold, respectively, with the presence of these findings. The study of Cho et al reported that 75% of patients with bowel transection showed a Janus sign near the site; therefore, it might be considered as a specific sign of bowel injury (6). With regards to mesenteric stranding, several studies showed that this feature was high sensitive but low specific to mesenteric injury (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced bowel-wall enhancement was confirmed when compared with that of the adjacent bowel wall (Figure 2). Janus sign was defined as a focal of increased-enhancement bowel loop adjacent to a focal decreased-enhancement one (6).…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Severe forms of bowel injury are rare and if reported usually follow high energy impact as seen in sports related injury [1] , [2] , motor vehicle accident [3] , [4] , [5] , [6] and falls from heights. Bowel transection has been reported following supposedly trivial trauma like coughing [7] fall from a bicycle [8] , child abuse [9] , [10] , hitting an iron fence bar [11] , handle bar trauma and others [12] .…”
Section: Introductionmentioning
confidence: 99%